Multidimensional poverty across ethnic groups: Disaggregating the global MPI - Alkire, S; Kovesdi, F (Oxford Poverty and Human Development Initiative (OPHI), 2020)
It is vital to document inequalities across ethnic groups to inform policies that can enable inclusive poverty reduction measures and prioritise the poorest. The Sustainable Development Goals (SDGs) demand greater disaggregation of indicators in order to make visible the inequalities that exist across social groups. This briefing presents disaggregations of the global Multidimensional Poverty Index (MPI)2 by ethnicity for the 24 countries and 650 million people whose current surveys present figures by ethnic group.